2000
DOI: 10.1097/00001756-200004070-00030
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory based spatial learning in neonatal mice and its dependence on CaMKII

Abstract: Spatial learning and memory involves the ability to encode geometric relationships between perceived cues and depends critically on the hippocampus. Visually guided spatial learning has been demonstrated in adult animals. As infant animals rely heavily on olfaction, olfactory based spatial learning was assessed in infant mice. When 12-day-old pups were displaced from their nest, they learned within a few training trials to use the spatial pattern of odor cues to move back to the nest. However, mouse pups that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
3
15
0
1
Order By: Relevance
“…Though previous work has shown that infant mice display preferences for maternal and homecage odors (Logan et al 2012; Thomas et al 2010) and are able to form conditioned memories (Akers et al 2012; Alleva & Calamandrei 1986; Bollen et al 2012; Bouslama et al 2005; Drake et al 2011; Durand et al 2003; Nagy et al 1972; Wiedenmayer et al 2000), to our knowledge, our data here are the first to show preference learning in infant mice despite an aversive conditioning paradigm, and thus are first to illustrate a sensitive period for attachment-based learning. Similar to developing rats, infant mice display a stress hyporesponsive period (Cirulli et al 1994; D’Amato et al 1992; Schmidt et al 2003).…”
Section: Discussionmentioning
confidence: 48%
“…Though previous work has shown that infant mice display preferences for maternal and homecage odors (Logan et al 2012; Thomas et al 2010) and are able to form conditioned memories (Akers et al 2012; Alleva & Calamandrei 1986; Bollen et al 2012; Bouslama et al 2005; Drake et al 2011; Durand et al 2003; Nagy et al 1972; Wiedenmayer et al 2000), to our knowledge, our data here are the first to show preference learning in infant mice despite an aversive conditioning paradigm, and thus are first to illustrate a sensitive period for attachment-based learning. Similar to developing rats, infant mice display a stress hyporesponsive period (Cirulli et al 1994; D’Amato et al 1992; Schmidt et al 2003).…”
Section: Discussionmentioning
confidence: 48%
“…In transgenic mice this test has revealed behavioral deficits in two different animal model of Down syndrome [4,67], in mouse pups over-expressing CaMKII [168] and in mouse pups lacking the mu opioid receptor [99]. The different mouse lines represent the different aspects of neonatal behavior that are actually targeted by the homing test.…”
Section: Homing and Social Odor Preferences In Neonatesmentioning
confidence: 99%
“…However, normal learning was shown in several non-hippocampusdependent learning tasks, such as the visible platform water maze, plus maze, cued Barnes maze, olfactory discrimination, the acquisition of instrumental conditioning, and the accelerating rotarod (Silva et al, 1992b;Bach et al, 1995;Giese et al, 1998;Wiedenmayer et al, 2000;Carvalho et al, 2001;Elgersma et al, 2002).…”
Section: Other Phenotypesmentioning
confidence: 99%